2021
DOI: 10.1089/aid.2021.0044
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: HIV Viral Load Trends During the Coronavirus Disease 2019 Pandemic in a Reference Center for HIV in Rome, Italy

Abstract: Coronavirus disease 2019 (COVID-19) pandemic has reduced the access of HIV patients to reference centers. However, retention-in-care is critical to maintain adherence to therapy and viral suppression. During lockdown in Italy, our center implemented several measures to ensure HIV-care continuum. To assess whether these efforts were successful, we investigated HIV viral load trend for a 1-year period (September 2019-August 2020), which included lockdown and partial lockdown months in our country. No significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Our findings are consistent with another Australian study involving an online survey for 153 PLHIV in Victoria, which reported 98% of PLHIV having self-reported access to ART during the pandemic [ 9 ]. Moreover, this study describes no change in the proportion of controlled viral load in Melbourne, which is in alignment with the findings in Rome, Italy [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are consistent with another Australian study involving an online survey for 153 PLHIV in Victoria, which reported 98% of PLHIV having self-reported access to ART during the pandemic [ 9 ]. Moreover, this study describes no change in the proportion of controlled viral load in Melbourne, which is in alignment with the findings in Rome, Italy [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
“…One study reported no significant difference in the number of ART collection visits in South African clinics, while another study reported a 23.1% reduction in the number of patients with ART scripts during the pandemic in Italy; however, this might be due to different COVID-19 situations and restrictions across countries [ 6 , 7 ]. In terms of impact on the viral load, a study conducted in Rome described no significant change in the proportion of undetectable viral load during the lockdown [ 8 ]. In Australia, a study reported that 98% of PLHIV in Victoria had self-reported access to ART; however, there are currently no published studies using a direct measure from medical clinics on the impact of the COVID-19 pandemic and lockdown restrictions on medication access and viral load control of PLHIV in high-income countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%